Calix[4]pyrrole macrocycle: Extraction of fluoride anions from aqueous media - Abbas, Ismail Ibrahim; Hammud, Hassan Hasan; Shamsaldeen, Hasan (European Journal of Chemistry, 2012)
Solid-phase extraction of fluoride anions by calixpyrrole macrocycle (CP) from aqueous media has been studied using the batch method. Various significant extraction parameters like initial concentration of the anion, extraction time, concentration of the calixpyrrole, pH and temperature were evaluated. Langmuir, Freundlichand, Dubinin-Redushkevish (D-R) isotherms and coefficients were used to analyze the equilibrium data. The amount of fluoride anion extracted per unit of the CP was found to be 0.40 mg/g at 298 K from 19 mg/L aqueous solution of fluoride anions. The mean free energy calculated from D-R model for the removal of fluoride anions by the CP was found to be 10.0 kJ/mol, indicating that chemisorption is involved in the extraction process. The data were also fitted to kinetic models such as pseudo first order and pseudo second order. The removal of fluoride anions increased with increasing temperature indicating the endothermic nature of the extraction process. The present method has been compared with the previous methods.